Modification of Durian Peel-Based Activated Carbon with Silver Nanoparticles for Enhanced Antibacterial Properties: A Literature Review - Pratiwi, Pina Budiarti; Tarigan, Ayu Syufiatun Br; Hasibuan, Adelia Yesya Putri; Yanti, Elsa Novri (Indonesian Journal of Science and Pharmacy, 2025)
Durian (Durio zibethinus) peel, an abundant agricultural waste in Southeast Asia, represents a sustainable lignocellulosic precursor for producing activated carbon (AC) with high surface area and porous structure. However, pristine durian peel-derived AC exhibits limited intrinsic antibacterial activity, primarily relying on physical adsorption. Silver nanoparticles (AgNPs) are well-known broad-spectrum antibacterial agents that disrupt bacterial membranes, generate reactive oxygen species (ROS), and interfere with cellular processes. Immobilization of AgNPs onto AC is expected to create a synergistic composite that combines adsorptive capacity with potent bactericidal effects. This literature review systematically examines the synthesis and characterization of activated carbon from durian peel, green synthesis routes of AgNPs using durian peel extract or pectin as reducing and stabilizing agents, and the potential of AgNP-modified durian peel AC for enhanced antibacterial performance. Key findings indicate that chemical activation (KOH or acid-based) yields AC with surface areas ranging from 257 to 666 m²/g. Pectin extracted from durian peel enables eco-friendly synthesis of stable, spherical AgNPs (core size ≈13.5 nm, zeta potential ≈ –50 mV) with minimum inhibitory concentrations (MIC) of 61.8 ppm against both Gram-negative Escherichia coli and Gram-positive Staphylococcus aureus. Comparative analysis reveals that while pristine durian peel AC shows only moderate bacterial capture, AgNP integration significantly improves bactericidal efficacy through combined adsorption-bactericidal mechanisms. Potential applications include water disinfection, antimicrobial filters, and biomedical materials. Challenges such as silver leaching, scalability, and long-term stability are discussed. This review highlights the emerging potential of AgNP-modified durian peel activated carbon as a low-cost, multifunctional material for addressing bacterial contamination while promoting waste valorization. Future research should focus on direct composite synthesis, comprehensive antibiofilm testing, and real-matrix performance evaluation.